(untitled) (Praxis Educativa, 2025)
This Dossier, "Frantz Fanon: 100 Years. His Influence on Latin American Intercultural Studies," presents five works on his thought. Fanon constitutes a radical critique of colonization, which is based on dehumanizing, violating, subjugating, and oppressing, with a clear challenge to decolonization as an inevitable and necessary act to dismantle the system of domination.